2011
DOI: 10.1177/0269216311425709
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus aureus (MRSA) management in palliative care units and hospices in Germany: A nationwide survey on patient isolation policies and quality of life

Abstract: Background: For palliative care settings, little is known about the benefits of specific methicillin-resistant Staphylococcus aureus containment regimens and the burdens patient isolation imposes on affected patients, their families, and professional caregivers. Aim: To explore the current practice of MRSA management and its impact on inpatients' quality of life as perceived by professional caregivers. Design: Survey of inpatient palliative care institutions using 23-item questionnaires (infrastructural data: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 21 publications
1
34
0
4
Order By: Relevance
“…Our results were similar to the findings of previous studies of caregivers of cancer patients; that is, previous studies showed that 20% of caregivers provided fulltime or constant care (Bukki et al, 2011), 5-20% of caregivers had quit their jobs or declined advancement as a result of caregiving (Dybicz et al, 2011;Fairfield et al, 2012;Pantilat et al, 2012). Fatigability was also a major reason for not working among cancer survivors in previous studies (Phipps et al, 2011;Flannelly et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results were similar to the findings of previous studies of caregivers of cancer patients; that is, previous studies showed that 20% of caregivers provided fulltime or constant care (Bukki et al, 2011), 5-20% of caregivers had quit their jobs or declined advancement as a result of caregiving (Dybicz et al, 2011;Fairfield et al, 2012;Pantilat et al, 2012). Fatigability was also a major reason for not working among cancer survivors in previous studies (Phipps et al, 2011;Flannelly et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…For example, several studies have documented typically high levels of dailyliving assistance, including help with transportation, shopping, homemaking, emotional support, nutritional care, nursing care, and personal care (Shahmoradi et al, 2009;O'Connor and Kumar, 2012;Stiel et al, 2012). As a result of daily-living assistance, many studies focused on family caregiver burdens such as high levels of stress, poor physical condition, emotional health, and family savings losses (Bukki et al, 2011;Duclos et al, 2012;Gomes et al, 2012;von Gunten, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, hospital-based PC units were more likely to report that MRSA control protocols have a negative impact on patients' quality of life (P < .001). 3 Conclusions A significant proportion of hospitalized PC patients with advanced cancer in our institution is MRSA positive. Further research is warranted to study the impact of MRSA control protocols on the quality of PC delivered to terminally ill patients.…”
Section: Discussionmentioning
confidence: 87%
“…2 In hospital-based palliative care (PC) units, the MRSA-positive patients receive what may be perceived as an aggressive care near the end of life like isolation and restriction of activities. 3 While an important issue, little is known about the prevalence of MRSA colonization and infection in hospitalized PC patients.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous studies showed that 20% of caregivers provided fulltime or constant care (Bukki et al, 2013); 5-20% of caregivers had quit their jobs or declined advancement as a result of caregiving (Dybicz et al, 2011;Fairfield et al, 2012;Pantilat et al, 2012). Fatigability was another major reason for unemployment among cancer survivors in previous studies (Phipps et al, 2011;Flannelly et al, 2012).…”
Section: Discussionmentioning
confidence: 98%